Quality of Care after Acute Coronary Syndromes in a Prospective Cohort with Reasons for Non-Prescription of Recommended Medications - Auer, Reto (Public Library of Science, 2014)
BACKGROUND: Adherence to guidelines is associated with improved outcomes of patients with acute coronary syndrome (ACS). Clinical registries developed to assess quality of care at discharge often do not collect the reasons for non-prescription for proven efficacious preventive medication in Continental Europe. In a prospective cohort of patients hospitalized for an ACS, we aimed at measuring the rate of recommended treatment at discharge, using pre-specified quality indicators recommended in cardiologic guidelines and including systematic collection of reasons for non-prescription for preventive medications. METHODS: In a prospective cohort with 1260 patients hospitalized for ACS, we measured the rate of recommended treatment at discharge in 4 academic centers in Switzerland. Performance measures for medication at discharge were pre-specified according to guidelines, systematically collected for all patients and included in a centralized database. RESULTS: Six hundred and eighty eight patients(54.6%) were discharged with a main diagnosis of STEMI, 491(39%) of NSTEMI and 81(6.4%) of unstable angina. Mean age was 64 years and 21.3% were women. 94.6% were prescribed angiotensin converting enzyme inhibitors/angiotensin II receptor blockers at discharge when only considering raw prescription rates, but increased to 99.5% when including reasons non-prescription. For statins, rates increased from 98% to 98.6% when including reasons for non-prescription and for beta-blockers, from 82% to 93%. For aspirin, rates further increased from 99.4% to 100% and from to 99.8% to 100% for P2Y12 inhibitors. CONCLUSIONS: We found a very high adherence to ACS guidelines for drug prescriptions at discharge when including reasons for non-prescription to drug therapy. For beta-blockers, prescription rates were suboptimal, even after taking into account reason for non-prescription. In an era of improving quality of care to achieve 100% prescription rates at discharge unless contra-indicated, pre-specification of reasons for non-prescription for cardiovascular preventive medication permits to identify remaining gaps in quality of care at discharge. TRIAL REGISTRATION: ClinicalTrials.gov NCT01000701